Carbon Accumulation, Flux, and Fate in Stordalen Mire, a Permafrost Peatland in Transition. Issue 1 (14th January 2022) - Holmes, M. E.; Crill, P. M.; Burnett, W. C.; McCalley, C. K.; Wilson, R. M.; Frolking, S.; Chang, K.‐Y.; Riley, W. J.; Varner, R. K.; Hodgkins, S. B.; ,; ,; et al.
Abstract: Stordalen Mire is a peatland in the discontinuous permafrost zone in arctic Sweden that exhibits a habitat gradient from permafrost palsa, to Sphagnum bog underlain by permafrost, to Eriophorum ‐dominated fully thawed fen. We used three independent approaches to evaluate the annual, multi‐decadal, and millennial apparent carbon accumulation rates (aCAR) across this gradient: seven years of direct semi‐continuous measurement of CO2 and CH4 exchange, and 21 core profiles for 210 Pb and 14 C peat dating. Year‐round chamber measurements indicated net carbon balance of −13 ± 8, −49 ± 15, and −91 ± 43 g C m −2  y −1 for the years 2012–2018 in palsa, bog, and fen, respectively. Methane emission offset 2%, 7%, and 17% of the CO2 uptake rate across this gradient. Recent aCAR indicates higher C accumulation rates in surface peats in the palsa and bog compared to current CO2 fluxes, but these assessments are more similar in the fen. aCAR increased from low millennial‐scale levels (17–29 g C m −2  y −1 ) to moderate aCAR of the past century (72–81 g C m −2  y −1 ) to higher recent aCAR of 90–147 g C m −2  y −1 . Recent permafrost collapse, greater inundation and vegetation response has made the landscape a stronger CO2 sink, but this CO2 sink is increasingly offset by rising CH4 emissions, dominated by modern carbon as determined by 14 C. The higher CH4 emissions result in higher net CO2‐equivalent emissions, indicating that radiative forcing of this mire and similar permafrost ecosystems will exert a warming influence on future climate. Key Points: Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon